2022
DOI: 10.3390/jcm11030815
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effectiveness of Obstructive Sleep Apnea Treatment Using Optical Coherence Tomography to Evaluate Retinal Findings

Abstract: Retinal findings may change in patients with obstructive sleep apnea syndrome (OSAS). The present study aims to evaluate several retinal findings, such as macula layer thickness, the peripapillary retinal nerve fiber layer, and the optic nerve head in patients with OSAS, using optical coherence tomography (OCT); it also aims to monitor the result of several types of treatment of OSAS with OCT. A prospective comparative study was designed. Patients were recruited at a Sleep Unit of a University Hospital and und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“… 10 Additionally, a recent study found that patients who underwent treatment of OSA were found to have normalization of OCT abnormalities, presumably due to correction of their nocturnal hypoxemia. 11 Patients with peripheral nonperfusion and neovascularization should receive targeted retinal photocoagulation and/or vascular endothelial growth factor antagonist intravitreal therapy which is the mainstay of treatment of proliferative retinopathy. Heightened awareness of the potential role of OSA to cause retinal hypoxia may suggest a greater need for OSA screening in patients, especially diabetics, with peripheral retinal neovascularization, as treatment with CPAP may reduce retinal hypoxic burden.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Additionally, a recent study found that patients who underwent treatment of OSA were found to have normalization of OCT abnormalities, presumably due to correction of their nocturnal hypoxemia. 11 Patients with peripheral nonperfusion and neovascularization should receive targeted retinal photocoagulation and/or vascular endothelial growth factor antagonist intravitreal therapy which is the mainstay of treatment of proliferative retinopathy. Heightened awareness of the potential role of OSA to cause retinal hypoxia may suggest a greater need for OSA screening in patients, especially diabetics, with peripheral retinal neovascularization, as treatment with CPAP may reduce retinal hypoxic burden.…”
Section: Discussionmentioning
confidence: 99%